Penentuan Nilai SPF Sediaan Lotion Tabir Surya dari Ekstrak Hasil Maserasi Bertingkat Daun Asam Jawa (Tamarindus indica L.) - Dewi, Serlyna Mutiara; Suhartinah, Suhartinah; Nopiyanti, Vivin (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Tamarind leaves contain compounds that have conjugated chromophore groups from aromatic rings such as phenol and its derivatives that can absorb ultraviolet radiation at a wavelength of 200-400 nm. Lotion is a form of sunscreen preparation that is comfortable to use because it has a lower oil content. This research aims to determine whether tamarind leaves extract obtained through multilevel maceration can be made into a sunscreen lotion with good physical stability and quality, determine the SPF value of each and compare them. Multilevel maceration is used to extract tamarind leaves. Solvents used are in sequence from non-polar, semi-polar and polar. Three formulas containing n-hexane extract, ethyl acetate extract, and 70% extract; and one more as a negative control. The three formulas contain tamarind leaves extract have the same concentration, 5%. Each formula is then tested to determine its qualities by physically. The SPF value was measured using UV-Visible spectrophotometer instrument at a wavelength of 290-320 nm with 5 nm intervals. The research results showed that the lotion preparation with tamarind leaf extract had good physical quality and maximum ultraviolet protection category, with SPF value for Formula 1 namely 9,81±0,07; Formula 2 namely 11,65±0,17; and Formula 3 namely 12,32±0,52. Formula 3 has the best physical quality and SPF value among the other formulas.